Physiological and anatomical behaviour of two contrasting maize hybrids grown at high density sowing - Travaglia, Claudia Noemi (2014)
This study evaluated the physiological and anatomical traits of two contrasting maize hybrids subjected to high density sowing inorder to explain yield stability through yield component analysis and the relation between the grain yield capacities per plantaccording to individual growth. Experiment factors were two commercially important maize hybrids: DK190MGRR2 andDK670MG, which behave differently under stress, and two levels of plant density: 7 and 11 plant/m2high and recommended densityto favour the conditions of water stress respectively. The experiment was carried out in the west of Argentina under rainfedconditions and five replications. Physiological parameters (pigments and endogenous content of phytohormones, injury of cellmembranes, yield components) and anatomical parameters (stomatal bevhaviour, foliar and peduncles anatomy, xylem and phloemarea in vascular bundles) were analyzed. In this study, both maize hybrids showed a differential response to both sowing densities.The DK670 showed an increased yield (24 and 10 % at 7 and 11 plant/m2, respectively) due to enhanced individual yieldcomponents. This hybrid was differentiated by a higher stomatal density (7±1 in the abaxial side) and pigment amount (20%, mainlychl a) which led to a better photosynthetic ability. In addition, this hybrid showed the capacity to compensate damages derived fromstress, mesophyll leaf thickness and closer bundles associated with tolerance to drought, and abundance in endogenousphytohormones to cope with stress. The description of these characteristics in response to different plant densities is novel results,especially those related to anatomical analysis under the different treatments. This research shows that the ability of hybrids to takeadvantage of abundance of resources at lower populations is an imperative need for over-seasonal potential yield accomplishment.This could help select more appropriate management practices and contribute to production areas.